Peer substance use overestimation among French university students: a cross-sectional survey - Dautzenberg Bertrand; Riou Franca Lionel; Falissard Bruno; Reynaud Michel (BMC, 2010)
Abstract Background Normative misperceptions have been widely documented for alcohol use among U.S. college students. There is less research on other substances or European cultural contexts. This study explores which factors are associated with alcohol, tobacco and cannabis use misperceptions among French college students, focusing on substance use. Methods 12 classes of second-year college students (n = 731) in sociology, medicine, nursing or foreign language estimated the proportion of tobacco, cannabis, alcohol use and heavy episodic drinking among their peers and reported their own use. Results Peer substance use overestimation frequency was 84% for tobacco, 55% for cannabis, 37% for alcohol and 56% for heavy episodic drinking. Cannabis users (p = 0.006), alcohol (p = 0.003) and heavy episodic drinkers (p = 0.002), are more likely to overestimate the prevalence of use of these consumptions. Tobacco users are less likely to overestimate peer prevalence of smoking (p = 0.044). Women are more likely to overestimate tobacco (p < 0.001) and heavy episodic drinking (p = 0.007) prevalence. Students having already completed another substance use questionnaire were more likely to overestimate alcohol use prevalence (p = 0.012). Students exposed to cannabis prevention campaigns were more likely to overestimate cannabis (p = 0.018) and tobacco use (p = 0.022) prevalence. Other identified factors are class-level use prevalences and academic discipline. Conclusions Local interventions that focus on creating realistic perceptions of substance use prevalence could be considered for cannabis and alcohol prevention in French campuses.